Pengaruh Akuntabilitas, Kompetensi dan Independensi terhadap Kualitas Audit(Studi Empiris pada Auditor KAP di Jawa Tengah) - Hapsari, Sefie Kurnia; , Drs. Suyatmin Waskito Adi, M.Si (2016)
The purpose of this study was to examine the effect of the accountability, competence, and independence for the quality of audits. The population in this study is the auditor of KAP in Central Java. The sample was selected by purposive sampling method. The sample by 54 respondents found the auditors on 10 KAP in the city of Semarang and Solo. Primary data collection method used is questionnaire method. For hypotheses testing using multiple regression analysis. These results prove that the accountability, competence and independence effect on audit quality. So the higher attitude of accountability, competence and independence will improve the quality of audits.